Snapticon: Developing effective listening skills for group oral discussion - Ngah, Ezihaslinda; Fauzi, Wan Jumani; Mohd Radzuan, Noor Raha; Abdullah, Hazlina; Mohd Ali, Amy Zulaikha; Noor Azlinda, Zainal Abidin; Mohamad Fadzillah, Fathiah Izzati (Universiti Teknologi MARA Selangor, 2022)
In many higher education institutions (HEIs) around the world, one of the popular English oral assessments for ESL learners is group discussion. In group discussions, it is vital that they have the ability to manage topics in a discussion by knowing how to initiate a topic, expand on the topic, seamlessly shift from one topic to another as well as close the topic appropriately. Students are therefore required to utilise their verbal and non-verbal skills to actively interact with all group members. Listening and speaking skills are equally important for effective communication including participating in group oral discussion. In order to help ESL learners to be active participants in group discussions, a card game called Snapticon was created. Open-ended questionnaires were distributed to 25 respondents in the study and observations were made while the game was being played. It was found from the findings that the respondents were positive as they regarded the game as interesting and fun. Therefore, it can be concluded that Snapticon has the potential to be used as a learning material to help develop ESL learners’ effective listening skills in group oral discussions. Moreover, the use of Snapticon enables learners to be interactionally competent when participating in group oral discussions.